Multifunctionality of Integrated Plantation Polyculture Farming in Tasikmalaya Regency, West Java, Indonesia - Nuryati, Rina; Sulistyowati, Lies; Setiawan, Iwan; Noor, Trisna Insan; Faqihuddin; Bunda, Cici Aulia Permata (Asian Journal of Agriculture and Rural Development, 2022)
Resilience, independence and sovereignty have historically been successfully realized by local communities through diversification. In fact, diversification has been institutionalized in farming communities in dryland agroecosystems. This research uses a survey method to gather data from 250 farmers in Tasikmalaya Regency, West Java, Indonesia, who carry out integrated plantation polyculture farming (IPPF). The main variables of the multifunctional IPPF are economic, social, cultural and environmental functions as well as the welfare of the farmers involved in the IPPF. Primary data were collected through interviews using questionnaires and secondary data were obtained from various related parties. Primary data were tabulated and analyzed descriptively and quantitatively using Farmer Household Income Exchange Rate (FHIER) analysis. In general, the farmers stated that IPPF contributed to the economy of farmers and the community, has a high social function, and also has an environmental function. On average, IPPF farmers’ families in Tasikmalaya Regency are categorized as prosperous families (FHIER > 1). Farmer households spend more income to meet consumption needs (FHIER = 1.66) compared to IPPF production costs (FHIER = 22.94), and non-food consumption (FHIER = 4.88) was greater than food consumption (FHIER = 4.48).